THE POTENTIAL OF SUPPORTIVE REMEDIAL ENVIRONMENT FOR STROKE RECOVERY FACILITIES - Siti Sarah binti Herman; Lee Yee Wen; Nur Qamarina Sharom; Azreen Jihan Che Mohd Hashim (Journal of Islamic, Social, Economics and Development, 2022)
Stroke recovery facilities are significant segment in the general consideration ofstroke patients. The nature of stroke is seen as an ailment that causes an entire scope ofphysical, mental and emotional unsettling influences. Due to this, recovery facilities designshould consider the social mental needs of the stroke survivors other than centering therecuperation of their physical capacities. Therefore, this study aims to investigate the potentialof supportive remedial environment as a recuperating apparatus to support better passionateand physical wellbeing recuperation of stroke survivors. A mixed methodology was adapted,which included questionnaire surveys and a semi-structured interview with the threerehabilitation health professionals and thirty respondents who are either the patients orrelatives of the patients who received treatment at the rehabilitation centre. The semi-structuredinterviews were analysed using the content analysis method. Meanwhile, the questionnairesurveys were analysed using descriptive analysis. This study has identified that the majorlimitations of the current rehabilitation facilities were the absence of inpatient facilities, lackof social spaces as well as insufficient of space for various activities conducted. Due to this,such issues need an attention to be solved by the architects in designing the area with healingenvironment, as well as the government as a funder to smoothen the process of rejuvenatingthe healing centre.